Advances in the Treatment of Drug-Resistant Pediatric Epilepsy - Gonzalez-Giraldo, Ernesto; Sullivan, Joseph E. (Seminars in Neurology, 2020)
Epilepsy is a common disorder in children and adults that causes significant morbidity and affects many aspects of a patient's lives. Two-thirds of patients with epilepsy are controlled with established antiseizure medications, leaving a significant number of patients searching for other options. The purpose of this review is to provide an overview of recent advancements in the management of treatment-resistant epilepsy in pediatric patients. Recent publications have shown the efficacy of new pharmaceutical options such as fenfluramine and cannabidiol, some of which have been tested specifically in patients with childhood-onset epilepsy syndromes such as Dravet's syndrome and Lennox–Gastaut's syndrome. Furthermore, recent approval by the U.S. Food and Drug Administration of stiripentol has made available a previously difficult-to-obtain option for patients with Dravet's syndrome. Finally, implanted responsive neurostimulation devices for direct cortical stimulation and deep brain stimulation have shown efficacy in adult patients and may represent a thrilling new horizon for pediatric patients.
Keywords: treatment-resistant epilepsy; Dravet's syndrome; Lennox–Gastaut's syndrome